Optimization of entrainment and interfacial flow patterns in countercurrent air-water two-phase flow in vertical pipes - Wang, Yongzhi; Luo, Feng; Zhu, Zichen; Li, Ruijie; Sina, Mohammad (Frontiers in Materials, 2024)
This study investigates countercurrent air-water two-phase flow in vertical pipes with inner diameters of 26 mm and 44 mm and a height of 2000 mm, under controlled conditions to eliminate heat and mass transfer. Cutting-edge techniques were employed to measure the liquid film thickness (δ) and entrainment (e) within the annular flow pattern. The methodology involved a systematic comparative analysis of experimental results against established models, identifying the most accurate methods for predicting flow behavior. Specifically, the Schubring et al. correlation was found to most accurately predict e in 26 mm pipes, while the Wallis correlation was more accurate for 44 mm pipes. Additionally, interfacial shear stress was analyzed, confirming the high precision of the δ and e parameters. This research enhances the understanding of countercurrent air-water two-phase flow by providing reliable estimation methods for different pipe diameters and emphasizes the significance of accurately determining interfacial shear stress. Key findings include the identification of the most accurate models for different pipe sizes and addressing challenges in measuring δ and e under controlled conditions. The study's novelty lies in its comprehensive comparative analysis of existing models, leading to improved predictions of flow dynamics in vertical pipes, thereby contributing valuable insights into two-phase flow behavior in geosciences and environmental engineering .